2018
DOI: 10.5897/jssem2018.0697
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of farming practices in terms of carbon sequestration potential of mulberry and soil organic carbon stock

Abstract: Thus, in terms of SOCS also, the same farming practice is capable of earning carbon credit to the tune of 4.91 Mg ha-1 in comparison to the existing farming practice over a time period of three years. It is also worthy to mention that the particular altered farming practice as mentioned can even earn a carbon credit of 1.14 Mg ha-1 in terms of SOCS in comparison to the fallow land over the same period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…CSP of mulberry was calculated on hectare basis utilizing the dry weights of leaf and shoot moisture content and their respective carbon content as described by Kar et al, (2018). CSP = y. C. (100m).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSP of mulberry was calculated on hectare basis utilizing the dry weights of leaf and shoot moisture content and their respective carbon content as described by Kar et al, (2018). CSP = y. C. (100m).…”
Section: Methodsmentioning
confidence: 99%
“…This could be possibly because of higher yield of mulberry and nutrition in the said treatment which improved the growth attributes signalling for higher sequestration potential of carbon. Kar et al, (2018) reported that mulberry growing under moderate tillage with grass cover registered the highest leaf productivity and CSP of 38.72 t ha -1 year -1 and 6.90 t ha -1 year -1 , respectively in comparison to the existing farming practice (IT) registering the same two parameters as 38.16 t ha -1 year -1 and 6.54 t ha -1 year -1 , respectively.…”
Section: Potential Of Mulberrymentioning
confidence: 98%